Genetic Diversity of Phytophthora infestans (Mont.) de Bary in the Eastern and Western Highlands of Uganda - Ochwo, M. K. N.; Adipala, E.; Rubaihayo, P. R.; Olanya, M. (Journal of Phytopathology, 2002)
Eight isolates of Phytophthora infestans were recovered from late blight infected samples collected from the districts of Mbale and Mbarara in the Eastern and Western highlands of Uganda in 2001 and analysed using mitochondrial deoxyribonucleic acid (DNA) haplotype and Amplified Fragment Length Polymorphism (AFLP) markers. Polymerase chain reaction amplification with the P2 primer followed by digestion with MspI yielded a three-fragment pattern characteristic of isolates belonging to the US-1 clonal lineage; the polymorphism was confirmed by DNA sequencing. AFLP analysis yielded 60 markers, analysis of which clustered the Ugandan isolates with reference to US-1 isolates (US930258 and US940501). These results suggest that the examined Ugandan isolates belong to the US-1 clonage lineage